AKUNTANSI PEMBIAYAAN MUDHARABAH - Ali Mauludi AC (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2015)
Accounting of mudharabah financing is counting the cash and non-cash deposited by Shari’ah Banks to Mudharrib customers with the principle of sharing for results and for loss. Measurement and recognition of accounting be based PSAK 59 and PAPSI 2003. In mudharabah financing, there are three events, namely the success without constraints, failed because of an error of mudharrib and failed not because fault of mudharrib. In the process of financing returns there is on time, there is not timely. Returns are not timely due to failure caused by errors and omissions of management on the part mudharrib, it will be receivable and  mudharrib obliged to return . If the failure is caused a natural phenomenon and not due to negligence of mudharrib then the banks bear the losses.